The Moho Relief Beneath the Zagros Collision Zone Through Modeling of Ground-Based Gravity Data and Utilizing Open-Source Resources in Python - Ardestani, Vahid E.; Mousavi, Naeim (Pure and applied geophysics, 2023)
Seismic Moho depth is defined based on a significant seismic velocity change between the crust and the upper mantle. Receiver function studies provide the most reliable estimates of the Moho depth. However, they are limited to some profile strikes to the Zagros collision zone. Here, we present an automated inverse methodology to provide a 3D Moho relief beneath the Zagros collision zone. We use gravity data in a vast square to compute the Moho depth model to refine an initial Moho depth model obtained from shear wave tomography. The depths, estimated by long wavelength shear wave tomography initially derived for the entire Middle East, are considered for the initial depth model. This initial model is refined by using a very popular and robust method for nonlinear inversion accessible through open-source resources in Python. Our modeling results indicate that only a 100 kg/m 3 density contrast between the crust and the upper mantle is sufficient to provide the Moho depth values comparable to receiver functions. This is interpreted as the high density and mafic affinity of the lower crust beneath the Zagros collision zone. It appears the lower crust returns to eclogite in the deep part. Alternatively, the cratonic core of the Zagros keel has a small density leading to only a 100 kg/m 3 density contrast between the lower crust and the uppermost lithospheric mantle. The depths obtained by our inversion methodology are compared and assessed to other studies in the area of Moho relief modeling.